Culture, Wealth, Gender, Real Estate, and Consumption in China: It's a Boy. Issue 1 (2nd January 2023) - Hardin, William G.; Hu, Mingzhi; Lin, Zhenguo
Abstract: Culture and derivative institutions affect household wealth, consumption, and property rights and ownership. Cultural factors also influence the role children play in determining household consumption and wealth accumulation, including acquisition of real property. The present study extends research on these influences by focusing on cultural norms in China. Chinese cultural norms, including indulgent care of single children, a strong preference for sons, increasing competition in the marriage market, and the importance of homeownership in marriage, suggest that the number, gender, and age of children likely affect a household's consumption and investment behavior, especially as related to consumption and investment in real property. Using China Family Panel Studies' (CFPS) longitudinal data, we found that, after controlling for other factors, total wealth (consumption) for households with children was 17.8% (23.5%) more than that of households without children. More interestingly, further results show that households with male children have more wealth accumulation and more expenditure on total consumption, including real estate–related expenditures, with a higher likelihood of owning additional residential real estate when compared to households with no or female children. The positive effect associated with children on household wealth is largely due to increased housing wealth, including the ownership of additional residential units. The pattern of wealth and real estate ownership follows Chinese cultural and social norms.